EFFECT OF MICROBIOLOGICAL DRUG “FITOBIOSOL” ON THE GROWTH, DEVELOPMENT AND PRODUCTIVITY OF BROCCOLI - Buriev Khasan Chutbayevich; Akbarova Nargiza Sadirdin qizi (Journals Park Publishing, 2022)
The results of a study conducted to determine the effect of the microbiological drug “Fitobiosol” on the development and yield of broccoli are presented. The experiments also covered changes observed in broccoli cabbage.
Keywords: broccoli cabbage; microbiological drug; biopreparation